Investigation into the severity of factors predisposing construction projects to risks in Nigeria - Adedokun, Olufisayo Adewumi; Aje, Isaac Olaniyi; Agboola, Oladele Johnson (Penerbit Universiti Kebangsaan Malaysia, 2019)
Factors predisposing construction projects to risks have received extensive attention in the literature at the detriment of the level of severity. This study aims at assessing the severity of these factors in Rivers State, Nigeria, with recourse to the perceptions of construction stakeholders. In achieving the aim; primary data were collected through questionnaires survey administered on284respondentsout of which 158 received formed the basis of analysis. The respondents were directly involved in the completed projects. Cronbach alpha test with a value of 0.902 attested to the high degree reliability of instrument used in collecting the data. Kruskal Wallis H test confirmed the convergent views of the respondents. The highly rated factors found predisposing construction projects to risks included excessive approval procedures in administrative government department/bureaucracy, inadequate contractors experience, contractor’s poor site management and supervision, inadequate programme scheduling and incomplete or inaccurate cost estimate among others. Having ascertained the significant severe factors predisposing construction projects to risk, administrative bottlenecks in securing approvals should be reduced coupled with allowance for adequate time to cater for approval formalities in government department. Also, experience of the contractor should also be given utmost priority as part of the criteria for selection to be fulfilled because it will not only enhance the project but also guide against poor site management and supervision. Lastly, there should be flexibility in the program schedule without affecting the overall project program while adequate attention should be accorded the cost estimates to ensure correctness.